Brain size does not predict general cognitive ability within families - Schoenemann, P. Thomas (The National Academy of Sciences, 2000)
Hominid brain size increased dramatically in the face of apparently severe associated evolutionary costs. This suggests that increasing brain size must have provided some sort of counterbalancing adaptive benefit. Several recent studies using magnetic resonance imaging (MRI) have indicated that a substantial correlation (mean r = ≈0.4) exists between brain size and general cognitive performance, consistent with the hypothesis that the payoff for increasing brain size was greater general cognitive ability. However, these studies confound between-family environmental influences with direct genetic/biological influences. To address this problem, within-family (WF) sibling differences for several neuroanatomical measures were correlated to WF scores on a diverse battery of cognitive tests in a sample of 36 sibling pairs. WF correlations between neuroanatomy and general cognitive ability were essentially zero, although moderate correlations were found between prefrontal volumes and the Stroop test (known to involve prefrontal cortex). These findings suggest that nongenetic influences play a role in brain volume/cognitive ability associations. Actual direct genetic/biological associations may be quite small, and yet still may be strong enough to account for hominid brain evolution.